2001
DOI: 10.1002/bem.81.abs
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic field of mobile phones affects visual event related potential in patients with narcolepsy

Abstract: The effects of the mobile phone (MP) electromagnetic fields on electroencephalography (EEG) and event-related potentials (ERP) were examined. With regard to the reported effects of MP on sleep, 22 patients with narcolepsy-cataplexy were exposed or sham exposed for 45 min to the MP (900 MHz, specific absorption rate 0.06 W/kg) placed close to the right ear in a double blind study. There were no changes of the EEG recorded after the MP exposure. A subgroup of 17 patients was studied on visual ERP recorded during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…In addition, the increase of EEG power during sleep included a broader frequency range after bstat exposure (Borbély et al, 1999;Huber et al, 2000) than after handset exposure (Huber et al, 2002). Thus, inconsistent results in the analysis of event-related brain potentials during RF EMF exposure might be in part related to differences in the modulation paradigms (Eulitz et al, 1998;Freude et al, 1998;Jech et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the increase of EEG power during sleep included a broader frequency range after bstat exposure (Borbély et al, 1999;Huber et al, 2000) than after handset exposure (Huber et al, 2002). Thus, inconsistent results in the analysis of event-related brain potentials during RF EMF exposure might be in part related to differences in the modulation paradigms (Eulitz et al, 1998;Freude et al, 1998;Jech et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, however, previously reported changes in cognitive functioning could not be replicated (Haarala et al, 2003b;Krause et al, 2004). Also, the analysis of event-related brain potentials during RF EMF exposure revealed conflicting results (Eulitz et al, 1998;Freude et al, 1998;Jech et al, 2001). It is possible that some inconsistencies are related to the spectral content of the applied RF EMF.…”
Section: Introductionmentioning
confidence: 94%
“…The authors hypothesized that RF EMF exposure modulates the response of EEG oscillatory activity around 8 Hz specifically during cognitive processing . In a recent study in narcoleptics, effects of RF EMF exposure on visual event-related potentials were observed and reaction times were reduced [Jech et al, 2001].…”
Section: Introductionmentioning
confidence: 98%
“…It was also found to be specific to the side of the brain directly exposed to the field. Similarly, in narcoleptic patients, Jech et al [2001] reported effects on two specific components of the EEG evoked by the presentation of rare (oddball) stimuli on the right half of the visual field. Field-dependent changes in the EEG have been reported in healthy volunteers exposed to pulsed 902 MHz fields during performance of either an auditory task or a visual memory task .…”
Section: Effects On the Eegmentioning
confidence: 94%